Pieniądz jako towar fikcyjny – utopia liberalizmu według Karla Polanyiego - Kozubowski, Jan (Annales. Etyka w Życiu Gospodarczym, 2020)
This article concerns Karl Polanyi’s theory of money as a fictitious commodity and its importance for understanding liberal ideology. According to the Hungarian economist, money is not a commodity but a social relation between the debtor and the creditor. Therefore, the complete commodification of money is part of a liberal utopia, as it is associated with a counter-movement and an economic crisis, two processes that make impossible the constitution of a market society. The author analyzes the problem of counter-movement through the prism of Karl Mannheim’s theory of utopia and ideology. The final part of the article deals with the problem of economic crises, Polanyi’s views on the nature of economic breakdown are compared with contemporary reflection on the role of money in financial markets.